Analysis of Li-Ion Battery Cell Internal Impedance Changes Based on Temperature and Soh - Biľanský Juraj; Ivan Jozef; Bodnár Dávid; Lacko Milan (Acta Electrotechnica et Informatica, 2022)
The paper is focused on the analysis of changes in the internal impedance of the selected battery cell. In addition, the paper describes basic information about these batteries, their advantages/disadvantages and possible uses. Battery data was obtained using our own testing device, which performed long-term cyclical tests on batteries to decrease SOH. Thanks to these tests, we obtained batteries with different SOH used for further measurement and evaluation. The internal impedance of selected batteries was measured with an accurate measuring device. Based on these measured data, the analysis described in this paper was created.